A concepção behaviorista da linguagem de W. V. O. Quine: exposição e defesa - Oliveira, Debora Fontoura de (2009)
To present dissertation it is the result of an investigation on the conception behaviorist of the language of Quine, tends as pretension your exposition and defense, alleging your permanence in elapsing of all the quinean works. The importance of this work is due to the fact that many critics were made Quine with regard to your linguistic perspective. Among the critics, what promotes contusing objections, it is Noam Chomsky. This alleges that Quine suffers from inconsistency and incoherence when proposing your language conception, and he still affirms that Quine abandons the behaviorism in your last works in favor of a mentalism. To accomplish the defense of Quine front to the accusations of Chomsky it was had as reference Roger Gibson, which elaborated a defense of the position of Quine, that however it was not very clear. This way, in this dissertation it is made an analysis not only of the critics of Chomsky, but also of the defense of Gibson in the search of offering a better explanation of the conception of Quine. It is sustained that the program behaviorist quinean is presented mainly in Word and Object, published in 1960, but it stays until your last publications. In these some are observed explanations and amplifications than it was already presented in 1960, but non incoherences. The sustentation of your conception is found in your rejection to the semantics traditional mentalist that accepts intension concepts as mental entities when correlating words with ideas. Quine defends that the linguistic meaning is a property of the behavior and, for this reason, not meeting differentiates comportamental, it is not possible to allege semantic difference. Quine assumes, then, that a perspective behaviorist is necessary for the study of the acquisition of the language, even if it is not enough. Besides, the defense of a behaviorism is not only important for your semantic aspect, but also epistemological, because Quine defends that the only possible road to understand the relationship between theory and world is, if before, the subject psychogenetic of "as it is acquired the language" it is answered. Starting from that, the conception behaviorist ends up assuming a central paper in the philosophy of Quine and, for the which, a lot of subjects are answered.